LOWER NORTH BATTERY - DEFENDED PORT OF SIMON’S TOWN - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
In 1975 Mr H. C. Willis suggested to the present writer that the SA Navy should mount a bronze plaque similar to those commissioned by the Simon’s Town Historical Society and displayed on certain historical buildings in the town at Lower North Battery to make people more aware of its long and fascinating history. Although a number of the Simon’s Town Port Record Books have been traced, that for Lower North Battery still cannot be found and important gaps in our knowledge of the battery’s history remain. Until these can be filled it is felt that it would be unwise to mount the plaque. Nonetheless, some valuable information has been traced and it is important that this should be placed on record.